2010
DOI: 10.1364/ao.49.000204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between quadratic approximation and δ expansion in studying the spreading of multi-Gaussian beams in turbulent atmosphere

Abstract: Based on quadratic approximation and delta expansion in the first order, the analytical expressions for multi-Gaussian beams in a turbulent atmosphere have been derived. By comparing the two approaches with numerical calculations, the relative errors of average intensity are investigated. As special cases, the relative errors for Gaussian beams, flattened Gaussian beams, and annular beams are investigated. The investigation shows that the method of delta expansion in the first order agrees well with numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Studies show that the relative error due to the expansion of hard aperture is less than 1% when the Fresnel number is smaller than one [20,22]. The relative error due to the firstorder expansion of exp½Àð= 0 Þ 5=3 in Taylor series has been examined [23,24]. Study shows that the relative error is smaller than 2.8% [24].…”
Section: General Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show that the relative error due to the expansion of hard aperture is less than 1% when the Fresnel number is smaller than one [20,22]. The relative error due to the firstorder expansion of exp½Àð= 0 Þ 5=3 in Taylor series has been examined [23,24]. Study shows that the relative error is smaller than 2.8% [24].…”
Section: General Theorymentioning
confidence: 99%
“…The relative error due to the firstorder expansion of exp½Àð= 0 Þ 5=3 in Taylor series has been examined [23,24]. Study shows that the relative error is smaller than 2.8% [24].…”
Section: General Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work showed that diverse intensity profiles could be obtained by choosing A n , w n and ϕ n . [18] On the basis of the extended Huygens-Fresnel principle, an expression for short-term average intensity was given in Ref. [2]…”
Section: General Theorymentioning
confidence: 99%
“…Our previous work showed that the first-order approximation of exp −x 5/3 could offer an accurate result to study MGB in turbulent atmosphere. [18] Following Ref. [18] the analytical formula for 014207-2 short-term average intensity can be derived as…”
Section: General Theorymentioning
confidence: 99%